Brief Report: Relationship Between Cotinine Levels and Peripheral Endogenous Concentrations of Oxytocin, β‐Endorphin, and Orexin in Individuals With Both Alcohol and Nicotine Use Disorders. Issue 1 (2nd June 2020) - Haass‐Koffler, Carolina L.; Perciballi, Roberta; Brown, Zoe E.; Lee, Mary R.; Zywiak, William H.; Kurtis, Jonathan; Swift, Robert M.; Leggio, Lorenzo
Abstract : Background and Objectives: In this secondary analysis of a pilot clinical trial with individuals with alcohol and nicotine use disorders, we investigate the relationship between serum concentrations of oxytocin, β‐endorphin, melatonin, α‐melanocyte‐stimulating hormone, substance P, and orexin, with objective biomarkers (salivary cotinine and serum γ ‐glutamyl transferase [GGT]) as well as with self‐reported smoking and alcohol drinking. Methods: Biomarkers for a total of N = 19 participants were analyzed using multiplexed, competitive format immune‐assay (peptides) and enzyme competitive immunoassay (saliva). A regression analysis using Pearson's correlation coefficient was utilized to determine correlations. We controlled for multiple comparisons, checked for collinearities, and ran two‐sided statistical tests. Results: We found significant positive correlations for cotinine and oxytocin ( P = .002), β‐endorphin ( P = .008), and orexin ( P < .001), but not for either GGT or self‐reported smoking or alcohol drinking. Conclusion and Scientific Significance: These preliminary results suggest a relationship between cotinine and oxytocin, β‐endorphin, and orexin, which opens up new potential hypotheses on the potential role of these endocrine pathways in tobacco smokers. (Am J Addict 2021;30:88–91)